The middleman - Steinhauer, Olen (Minotaur Books, 2018)
"This stunning stand alone from the author of New York Times bestseller The Tourist, follows the people on all sides of a domestic terrorist group, from the group's converts to the FBI agents investigating them. New York Times bestselling author Olen Steinhauer's next sweeping espionage novel traces the rise and fall of a domestic left-wing terrorist group. Told from the individual perspectives of an FBI agent, an undercover agent within the group, a convert to the terrorist organization, and a writer on the edges of the whole affair, this is another tightly wound thriller, and an intimate exploration of the people behind the politics, from a master of suspense"--